2007
DOI: 10.1007/s10531-007-9155-9
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and structural patterns for tropical montane and premontane forests of central Peru, with an assessment of the use of higher-taxon surrogacy

Abstract: The Chanchamayo valley in the Peruvian Andes formerly contained large areas of montane and premontane tropical forests, although logging and agricultural expansion has resulted in extensive deforestation and habitat fragmentation. This study evaluates the regional context of the valley by a comparison of data from a series of one hectare plots giving data on the diversity and structure of treeş 10 dbh, and then examines in more detail data from a 1 ha plot located in a newly declared conservation area (Pampa H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
21

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(47 citation statements)
references
References 47 publications
1
25
0
21
Order By: Relevance
“…In a study conducted in an Amazonian Peruvian hillside forest, the highest value recorded was 156 species/ha (GomezPeralta et al 2008), which is higher than the values recorded in the present study (~80 species/ha, Table 3). However, in other studies undertaken in Amazonian hillside forests, the biodiversity values recorded are similar to those reported in this study (120 species in a montane forest, La Torre-Cuadros et al 2007). Colombian Amazonian montane forest was considered the most important in the world in terms of biodiversity (Gentry 1982) although the richness value recorded in Colombia was 72.3 species/ha ±18 (Aubad et al 2008), which is only a little higher than the value recorded in our study.…”
Section: Compositionsupporting
confidence: 91%
“…In a study conducted in an Amazonian Peruvian hillside forest, the highest value recorded was 156 species/ha (GomezPeralta et al 2008), which is higher than the values recorded in the present study (~80 species/ha, Table 3). However, in other studies undertaken in Amazonian hillside forests, the biodiversity values recorded are similar to those reported in this study (120 species in a montane forest, La Torre-Cuadros et al 2007). Colombian Amazonian montane forest was considered the most important in the world in terms of biodiversity (Gentry 1982) although the richness value recorded in Colombia was 72.3 species/ha ±18 (Aubad et al 2008), which is only a little higher than the value recorded in our study.…”
Section: Compositionsupporting
confidence: 91%
“…ter Steege et al 2000a;La Torre-Cuadros et al 2007). While this may be enough to identify the major forest types, and indeed some studies in tropical forests do confirmed a positive correlation between the richness of the woody component of a forest and its accompanying non-woody component (e.g.…”
Section: Los Volcanes Plots In a Neotropical Contextmentioning
confidence: 99%
“…The continua delimit possible configurations of embedded landscapes; they influence biodiversity in spatial ways, increasing beta diversity and other place-to-place heterogeneity (e.g., Kattan et al, 2006) and affecting genetic variation (Ohsawa & Ide, 2008). Change in elevation in the Andes produces a series of interrelated shifts in atmospheric gases, solar radiation, wind, temperature ranges, and soil moisture (Körner, 1999), not to mention in species composition (e.g., Terborgh, 1971;La Torre-Cuadros et al, 2007;Sergio & Pedrini, 2007).…”
Section: Spatial Dimensions Operating In Andean Landscapesmentioning
confidence: 99%